Design of an Educational Game for Children: 'Geometry Forest' Using Construct 2 - Retno, Sujacka (Gameology and Multimedia Expert, 2025)
Early childhood education plays a crucial role in building the foundational knowledge and skills that will be used throughout life. This study aims to design and develop an educational game titled "Geometry Forest" using Construct 2, specifically designed to help children understand basic geometry concepts through an interactive and engaging learning experience. The game integrates learning elements such as recognizing geometric shapes, identifying colors, and enhancing cognitive and motor skills, with attractive graphics and a user-friendly interface. The development process includes concept design, asset creation, implementation, and testing, involving young children to evaluate their engagement, enjoyment, and understanding of the material presented. The results show that "Geometry Forest" effectively improves understanding of geometric concepts while providing an enjoyable learning experience, making it a valuable supplementary tool for learning both at school and home, and contributing to the improvement of early childhood education quality through educational game technology.